A Palindromic CpG-Containing Phosphodiester Oligodeoxynucleotide as a Mucosal Adjuvant Stimulates Plasmacytoid Dendritic Cell-Mediated T(H)1 Immunity - Maeyama, Jun-ichi (Public Library of Science, 2014)
BACKGROUND: CpG oligodeoxynucleotides (ODNs), resembling bacterial DNA, are currently tested in clinical trials as vaccine adjuvants. They have the nuclease-resistant phosphorothioate bond; the immune responses elicited differ according to the CpG ODN sequence and vaccination method. To develop a CpG ODN that can induce plasmacytoid dendritic cell (pDC)-mediated T(H)1 immunity through the mucosa, we constructed phosphodiester G9.1 comprising one palindromic CpG motif with unique polyguanosine-runs that allows degradation similar to naturally occurring bacterial DNA. METHODS: T(H)1 and T(H)2 immunity activation was evaluated by cytokine production pattern and T-bet/GATA-3 ratio in human peripheral blood mononuclear cells and mouse bone marrow cells. Adjuvanticity was evaluated in mice administered G9.1 with diphtheria toxoid (DT) through nasal vaccination. RESULTS: G9.1 exhibited stronger IFN-α-inducing activity than A-class CpG ODN2216 and increased T-bet/GATA-3 ratio by enhancing T-bet expression. Nasally administered G9.1 plus DT induced DT-specific mucosal IgA and serum IgG, but not IgE, responses with antitoxin activity in C57BL/6 and BALB/c mice, possibly due to IFN/BAFF production. Induction of T(H)1, but not T(H)2, -type Abs depended completely on pDCs, the first in vivo demonstration by CpG ODNs. CONCLUSIONS: G9.1 is a promising mucosal adjuvant for induction of pDC-mediated T(H)1 immunity.